Effect of Al Concentration over ZnO-Al2O3 Physicochemical Characteristics and Removal of Remazol Red RB - Widia Purwaningrum; Fingky Pristika Sari; Julinar Julinar; Adiq Ahmadi; Muhammad Said (Department of Chemical Engineering, Universitas Gadjah Mada, 2022)
ZnO is one of the widely used semiconductors due to its high photocatalytic activity. The inactivity of ZnO in the visible range could be enhanced by combining the ZnO with Al. In this study, the photocatalytic activity of ZnO-Al2O3 on Remazol Red RB was investigated. The effect of the ratio mass of ZnO-Al2O3 (1:0.05, 1:0.07, and 1:0.10) was also evaluated. The photocatalyst would be characterized using XRD, SEM-EDX, and UV-Vis DRS. The characterization showed that photocatalysts were successfully synthesized. The XRD analysis showed that the optimum ratio mass of ZnO-Al2O3 was achieved by 1:0.05, with the smallest crystal size of 13.3 nm. The SEM analysis showed that the surface of ZnO-Al2O3 (1:0.05) was easily granulated with smaller particle sizes than ZnO, and the shape tends to clump with the composites. The EDX analysis of ZnO-Al2O3 confirmed the presence of Zn, O, and Al elements. The photodegradation study showed that the optimum conditions were obtained at a contact time of 180 minutes at pH 6 with 91.04% dye removal. In addition, the effect of the initial concentration of the dye was achieved at 50 ppm with a dye removal of 89.26%. The study showed that the ZnO-Al2O3 exhibited adequate removal of Remazol red RB.